Memory in neurodegenerative disease : biological, cognitive, and clinical perspectives - Tröster, Alexander I. (Cambridge University Press, 1998)
Presents current information about memory disorders in Alzheimer's, Huntington's and Parkinson's diseases and in other neurodegenerative conditions. Diagnosis, assessment and treatment issues are discussed, as are ethical and legal considerations. An essential reference for clinicians and neuroscientists.